Adapting emotional support in teams: productivity, emotional stability, and conscientiousness - Saccardi, Isabella; Masthoff, Judith (Frontiers in Artificial Intelligence, 2025)
Students' mental health has received increased attention in recent years: reports of worsened mental health among higher education students call for new ways to support them in their college years. Educational demands are among the concerns that students report, such as the stress of academic performance, the stress related to examinations and the pressure to succeed. One aspect often present in higher education is group work. Group work can be truly beneficial for learning, but it often causes additional stress to students. The present research contributes to the design of a peer assessment tool to support students during group work. In this tool, each student is asked to rate their teammates on several aspects of group work, and a virtual agent delivers support statements in response to such ratings. For the support statements to be appropriate, the virtual agent should adapt them to the recipient and the group work situation they are experiencing. We investigate the adaptation of emotional support statements to the student's personality trait of Conscientiousness and the score assigned to a teammate on one aspect of teamwork, Productivity. The resulting algorithm is then combined with related work on Emotional Stability, and a final algorithm considering both dimensions is created.